2018
DOI: 10.12659/msm.910059
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the KINDLIN-2 Gene and Reduced Expression of Kindlin-2 Affects Vascular Permeability in Angiogenesis in a Mouse Model of Wound Healing

Abstract: BackgroundAngiogenesis is an important component of wound healing and tissue repair. Kindlin-2 is an integrin-associated protein, encoded by the KINDLIN-2 gene, which has been shown to affect cell adhesion and migration of cells, including endothelial cells. The aim of this study was to use a mouse model of wound healing to evaluate the effects of expression of KINDLIN-2 on angiogenesis in wound healing in vivo.Material/MethodsThirty-six male C57BL/6 mice were studied in an established model that used a wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Our previous study showed that kindlin-2 affects neovascular permeability [20], and here, we detected whether its expression in melanoma cells had an effect on angiogenesis. We found that kindlin-2 overexpression in melanoma cells promoted vascular formation and that the downregulation of kindlin-2 inhibited vascular formation (Figure 3A).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Our previous study showed that kindlin-2 affects neovascular permeability [20], and here, we detected whether its expression in melanoma cells had an effect on angiogenesis. We found that kindlin-2 overexpression in melanoma cells promoted vascular formation and that the downregulation of kindlin-2 inhibited vascular formation (Figure 3A).…”
Section: Resultsmentioning
confidence: 73%
“…Previously, we indicated that neovascular permeability was increased and blood vessels were shorter and thinner in kindlin-2 gene knockdown mice [20]. Liao et al [24] showed that kindlin-2 is necessary for angiogenic sprouting in vitro and for tumour angiogenic development in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work suggested that kindlin-2 interacts with endothelial adherens junctions to support vascular barrier integrity ( Pluskota et al. 2017 ) and a knockdown of this gene increases neovascular permeability ( Ying et al. 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kindlin‐2 has been shown to promote tumour invasion and metastasis 54,55 . It is also essential for preserving integrity of the heart, vascular permeability in angiogenesis, chondrogenesis, regulation of podocyte structure and function, control of adipogenesis and lipid metabolism as well as bone homeostasis 56‐61 . Kindlins protect cells against oxidative damage 62‐65 .…”
Section: Discussionmentioning
confidence: 99%